Complete postsurgical left ventricular‐aortic discontinuity and pseudoaneurysm formation. Issue 7 (29th April 2022) - Fu, Weibo; Davari, Paran; Issa, Mohamed; Alslaim, Hossam; Cortese, Nia; Bates, William B.; Ferraris, Victor; Winkler, Michael
Abstract: Background: Left ventricular outflow tract pseudoaneurysm is a rare but potentially fatal complication of aortic valve replacement, infective endocarditis (IE), and suture dehiscence. Left ventricular‐aortic discontinuity is a severe and uncommon manifestation of IE. For patients who have a long‐standing history of endocarditis, periannular lesions in the aortic valve may rupture, leading to the rare occurrence of complete, or total, left ventricular‐aortic discontinuity. Methods: We present a case of complete postoperative left ventricular‐aortic discontinuity and massive circumferential left ventricular outflow tract pseudoaneurysm discovered during a 3‐month follow‐up visit. Appropriate consent was obtained from all parties before submission of this case report. Results: Postoperative cardiac computed tomography of a patient demonstrated dehiscence of a recently placed surgical aortic valve from the left ventricular outflow tract, with massive circumferential pseudoaneurysm formation. Only a small remnant of the membranous interventricular septum connected the aortic root to the heart, informing the diagnosis of complete left ventricular‐aortic discontinuity. Conclusion: The clinical presentation of a left ventricular outflow tract pseudoaneurysm with concomitant left ventricular‐aortic discontinuity is commonly nonspecific or clinically silent; thus, it requires a high index of suspicion and use of multimodality imaging for diagnosis and management.